2018
DOI: 10.1145/3185515
|View full text |Cite
|
Sign up to set email alerts
|

Using Machine Learning to Support Qualitative Coding in Social Science

Abstract: Machine learning (ML) has become increasingly influential to human society, yet the primary advancements and applications of ML are driven by research in only a few computational disciplines. Even applications that affect or analyze human behaviors and social structures are often developed with limited input from experts outside of computational fields. Social scientists—experts trained to examine and explain the complexity of human behavior and interactions in the world—have considerable expertise to contribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
86
1
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 125 publications
(90 citation statements)
references
References 37 publications
2
86
1
1
Order By: Relevance
“…More precisely, we took every 3rd sample from the test dataset and added it to the train dataset. We then performed 3-fold cross validation 5 . The results can be seen in Fig.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…More precisely, we took every 3rd sample from the test dataset and added it to the train dataset. We then performed 3-fold cross validation 5 . The results can be seen in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…The process is even further complicated by the need of producing annotation with high interrater reliability, which in itself includes training the coders for a given problem [32]. As the size of the data typically collected in studies increases [5], it becomes difficult, even impossible, to code the data manually.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of an ML approach, Abbas et al (2018) demonstrated a significant accuracy improvement over standard screening tools in a clinical study using a sample of 162 children. Despite the previous work, low precision has been considered a limitation with such approaches Chen et al (2018), therefore researchers still face challenges applying ML in this domain. Bone et al (2015) argue that clinical domain experts and computational researchers must cooperate in order to maximize the potential use of ML for behavioural science.…”
Section: Related Workmentioning
confidence: 99%
“…There is an increasing amount of work using cameras as the main sensor placed at a certain distance from the child to automatically recognise their behaviour with computer vision (CV) methods (Dawson et al, 2018; Hashemi et al, 2014, 2015; Manner, Jiang, Zhao, Gini, & Elison, 2017). Additionally, with the advances in ML, there has also been an increasing amount of work studying its application for automatic coding (Abbas, Garberson, Glover, & Wall, 2018; Bone et al, 2015; Chen, Drouhard, Kocielnik, Suh, & Aragon, 2018). There are issues that have been identified when using ML techniques, which are related to the lack of shared knowledge between problem‐domain and experts.…”
Section: Introductionmentioning
confidence: 99%